Speech Acts and Its Translation Accuracy in Bilingual Fables - Usep Muttaqin; Nadia Gitya Yulianita; Uki Hares Yulianti (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2020)
The study aims to analyze the type of speech act found in bilingual fables and its translation accuracy. The theory of Searle (1969) on the classification of speech act and the instrument of translation accuracy from Nababan et. al. (2012) are used in the study. It is a descriptive qualitative research with embedded-case study. Several fables books from several different publishers are taken as the data source. The result shows that there are seven pairs of speech act found in both SL and TL utterances, namely directive – directive, representative – representative, expressive - expressive, commissive – commissive, directive - representative, expressive – representative, and expressive directive. The first four pairs are in the same type of speech act whereas the last three pairs have different types of speech acts between SL and TL utterances. Those pairs with the same type of speech act are mostly translated accurately while those pairs with different type of speech act are translated less accurately and inaccurately.